Entrepreneurship Model: Attributes of Entrepreneurial Intention Between Exact And Non-Exact Students - Andi Yulianto; Roby Setiadi; Roni Roni (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Entrepreneurial intention in a person can be formed by the external and internal environment. This study examines the attributes entrepreneurial intentionin students : role models, entrepreneurial attitude, subjective norms, and emotional competence. The purpose of this study is to determine a model of entrepreneurial intention among exact and non-exact college students. in Brebes and Tegal, Central Java. Respondents observed were exact and non-exact students at three tertiary institutions, namely Muhadi Setiabudi University (UMUS) Brebes, Polteknik Harapan Bersama (Poltek Harber) Tegal, and Pancasakti University (UPS) Tegal with a total of 301 students using a cluster random sampling. This research uses a quantitative analysis approach with data analysis techniques Structural Equation Model (SEM), a method to test the attributes that make up the entrepreneurial intention model. The results showed that the exact entrepreneurial intention of the student group was formed by the attributes of entrepreneurial attitude, and emotional competence. Meanwhile, the non-exact student group was formed by the attributes of role models and entrepreneurial attitudes. The implication of this research is that universities can form entrepreneurial characters among students through a conducive and dynamic curriculum and academic atmosphere.